Relationship of Jigsaw-Type Cooperative Learning Model With Student Learning Outcomes - Lastri Lastri (Lembaga Intelektual Muda (LIM) Maluku, 2020)
This study aims to find out the relationship of jigsaw-type cooperative learning model with student learning outcomes on the concept of opportunity in grade XI SMK Muhammadiyah Ambon The type of research used is correlational quantitative, namely research. The sample in this study amounted to 28 people. The instruments used are tests and questionnaires. Tests are used to determine student learning outcomes and questionnaires are used to determine students' responses to jigsaw-type cooperative learning models. Data analysis techniques used are Product Moment Correlation. The results showed that there is a strong relationship between jigsaw-type cooperative learning models and students' learning outcomes in the opportunity material in smk Muhammadiyah Ambon class. Hypothetical test results using correlation test Products moment obtained r of 0.8374. While the conversion result based on the table of distribution of rtable value is obtained rtabel value at the level of 5 percent which is 0.374